Persistent thrombocytopenia following dengue shock syndrome - Kohli, Utkarsh (Indian J Pediatr, 2008)
Though thrombocytopenia is one of the hallmarks of dengue hemorrhagic fever/ dengue shock syndrome, persistence of the same is rare. We report an 11 year-old child with dengue shock syndrome, who developed persistent thrombocytopenia. The possible mechanisms are discussed.